1999
DOI: 10.1073/pnas.96.17.9509
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the biosynthetic gene cluster for the polyketide anthelmintic macrolide avermectin in Streptomyces avermitilis

Abstract: Analysis of the gene cluster from Streptomyces avermitilis that governs the biosynthesis of the polyketide anthelmintic avermectin revealed that it contains four large ORFs encoding giant multifunctional polypeptides of the avermectin polyketide synthase (AVES 1, AVES 2, AVES 3, and AVES 4). These clustered polyketide synthase genes responsible for avermectin biosynthesis together encode 12 homologous sets of enzyme activities (modules), each catalyzing a specific round of polyketide chain elongation. The clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
232
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 300 publications
(241 citation statements)
references
References 31 publications
2
232
0
3
Order By: Relevance
“…This loading AT-ACP didomain was identified at the N terminus of BfmA1, adjacent to the KS domain of module 1. A similar loading AT-ACP didomain has been reported in erythromycin 23 and avermectin 24 PKSs. Thus, all KS domains in bafilomycin PKS modules were functional (Supplementary Figure S1).…”
Section: Region Encoding Bafilomycin Pkssupporting
confidence: 77%
“…This loading AT-ACP didomain was identified at the N terminus of BfmA1, adjacent to the KS domain of module 1. A similar loading AT-ACP didomain has been reported in erythromycin 23 and avermectin 24 PKSs. Thus, all KS domains in bafilomycin PKS modules were functional (Supplementary Figure S1).…”
Section: Region Encoding Bafilomycin Pkssupporting
confidence: 77%
“…Because the biosynthetic pathways of both avermectin and filipin require malonyl-CoA and methylmalonyl-CoA as a common extender unit of the polyketide backbone (Ikeda et al, 1999;Omura et al, 2001), it is most likely that the delayed expression of the ave genes, attributed to the delayed and weakened transcription of aveR as the result of avaR3 disruption, would lead to the preferential use of precursors in filipin production at the middle growth stage, resulting in increased filipin production and a lack of the necessary precursors for avermectin production at the late growth stage. Regarding oligomycin production, although oligomycin biosynthesis shares common precursors (malonyl-CoA and methylmalonyl-CoA) with avermectin and filipin biosynthesis (Wei et al, 2006), because oligomycin production already reached a plateau before the onset of avermectin production in the wild-type strain ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthetic pathways of the three types of antibiotic have been predicted and partially elucidated (Ikeda et al, 1999;Omura et al, 2001), while genetic information on the regulatory mechanism of antibiotic production has so far been limited. With respect to avermectin production, we recently reported that AveR, which is encoded by a gene situated on the left-hand extremity of the avermectin biosynthetic gene cluster, is a positive LAL-family regulator for controlling avermectin biosynthetic genes .…”
Section: Introductionmentioning
confidence: 99%
“…Branched-chain starter substrates in the polyketide chain initiation reaction are required for production of highly branched polyketides. It was known that the acyltransferase (AT)-acyl carrier protein (ACP) loading didomain of the avermectin PKS could use a variety of molecules, including the branched chain acyl-CoAs, isobutyryl-and 2-methylbutyryl-CoA, 6,7 to initiate avermectin biosynthesis, but we were not able to produce a soluble, active loading didomain either as a stand-alone protein or linked to an extender module (module 1) that would give us the required diketide in vitro. Hence we turned to the lipomycin PKS, which was proposed to use isobutyryl-CoA to initiate α-lipomycin biosynthesis, and whose AT-ACP loading didomain is linked to module 1 to form the first polypeptide (LipPks1) of the PKS complex ( Figure 1a).…”
Section: Substrate Specificities Of Pks Domainsmentioning
confidence: 99%